Mitogen-activated protein kinase activation in lung adenocarcinoma: A Comparative study between ever smokers and never smokers - Mountzios, G.; Planchard, D.; Besse, B.; Validire, P.; Girard, P.; Devisme, C.; Dimopoulos, M.-A.; Soria, J.-C.; Fouret, P. (Clinical Cancer Research, 2008)
Purpose: There are major differences affecting genes in adenocarcinomas in ever and never smokers. However, data on whether mitogen-activated protein kinase (MAPK) activation state differs according to smoking status are limited. Experimental Design: Expression of activated extracellular signal - regulated kinases, c-Jun NH2-terminal kinases, and P38 enzymes (pP38) were evaluated by means of immunohistochemistry in 188 chemonaïve patients with surgically resected lung adenocarcinoma. Cell viability of the lung adenocarcinoma cell line HCC827 was studied after treatment with cisplatin or the P38 MAPK inhibitor SB 203580. Results: Thirty-seven of 44 never smokers [84%; 95% confidence intervals (95% CI), 70-92%] expressed high pP38 levels compared with 45 of 104 ever smokers (43%; 95% CI, 34-53%; P < 0.0001). The proportion of never smokers expressing high c-Jun NH2-terminal kinase levels (72%; 95% CI, 57-83%) was greater than that of ever smokers (53%; 95% CI, 44-62%; P = 0.03). The proportion of ever smokers expressing high extracellular signal - regulated kinase levels (51%; 95% CI, 42-59%) was similar to that of never smokers (57%; 95% CI, 42-71%; P = 0.47). Never smokers were 10.5 times (95% CI, 3.5-31.5) more likely to express high pP38 levels after adjustment for variables linked to smoking status, including age, sex, and histologic subtype. None of the activated MAPKs predicted for overall survival. Cell viability of HCC827 was significantly reduced after exposure to SB203580 alone or when combined with cisplatin. Conclusions: Life-long nonsmoking is associated with high activated P38 levels in patients with lung adenocarcinoma. Activated P38 can contribute to the viability of adenocarcinoma cells in never smokers, but is not predictive for overall survival. © 2008 American Association for Cancer Research.